(untitled) (University of Khartoum Engineering Journal, 2022)
Local scour for impermeable and permeable (slotted) spur dykes where tested at the lab. The experimental data were analyzed and compared for the two types of dykes. It is found that, for different sets of dykes arrangements, the local scour magnitude for permeable dykes is reduced significantly compared to that of impermeable ones. For the case of 5 spur dykes arranged on both sides of the flume the reduction in the local scour depth ranges between 16% to 51%, while for the set of 3 spur dykes arranged along one side of the flume is between 18% to 44% and for single spur dyke 30% to 62% . The generated eddy width for the case of a single spur dyke is noticed to be between 34% to 43% of the flume width B while the eddy length is found to range between 4 to 5 times the model spur length b. The contraction ratio has a significant effect in the magnitude of the local scour. The local scour depth corresponding to the middle spur of the set of five spurs (contraction ratio =60%) is equal to 2.6 times that corresponding to the same position of the set of three spurs (contraction ratio =80%) for impermeable dykes. For permeable dykes the ratio is equal to 3.